2022
DOI: 10.3390/en15062164
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization—The Engine of Sustainability in the Energy Industry

Abstract: The goal of this paper is to conduct a bibliometric analysis of the scientific literature about the sustainability of digitalization in the energy sector in order to capture the main challenges and trends in the transition towards it. The bibliometric analysis of the scientific literature was carried out by interrogating the Scopus database, using a set of keywords considered relevant for the analyzed field and for the goal of the proposed research. The purpose of the study was, on the one hand, the depth of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In other words, based on more rigorous statistical extrapolation results, intelligent manufacturing can improve TFEE, and the H1 is verified. The results of this study are consistent with the conclusions of existing studies [79]. By comparing the fitting coefficients of the three models in column (2), column (4), and column (5), it can be found that the TWFE model with all the control variables has the maximum estimated coefficient, the TWFE model with the control of the three variables has a smaller estimated coefficient, and the fitting coefficient of the POLS is at the minimum level.…”
Section: Baseline Regressionsupporting
confidence: 90%
“…In other words, based on more rigorous statistical extrapolation results, intelligent manufacturing can improve TFEE, and the H1 is verified. The results of this study are consistent with the conclusions of existing studies [79]. By comparing the fitting coefficients of the three models in column (2), column (4), and column (5), it can be found that the TWFE model with all the control variables has the maximum estimated coefficient, the TWFE model with the control of the three variables has a smaller estimated coefficient, and the fitting coefficient of the POLS is at the minimum level.…”
Section: Baseline Regressionsupporting
confidence: 90%
“…Considering that digitalization may benefit both efficiency and environmental performance [33,34], policies could be used to support the development and adoption of digitalized DH. Yet, the two views have different implications for the design of policy support for digitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The latter domain represents a group of technological solutions that enable efficient remote management of resources and processes [29] and therefore accommodate new business models for both the business-to-consumer [30,31] and business-to-business [32] segments. Digitalization has been identified as a driver of efficiency in addition to sustainability in the energy sector [33,34]. As such, digitalization is expected to have far-reaching impacts on the design of value offerings and value creation [6,12].…”
Section: Business Model Innovation and Digitalizationmentioning
confidence: 99%
“…The integration of digital technology in numerous daily activities has resulted in significant transformations in various aspects of life [4]. Covid-19 has accelerated the implementation of digital technologies in daily life [5]. The utilization of digitalization in manufacturing has brought about substantial alterations to the industry, creating competitive advantages for businesses [6], but has also resulted in changes of the needed skill sets and competencies of industrial engineers [7].…”
Section: Introductionmentioning
confidence: 99%